Scientific Production of Exoskeleton: A Scientometric Analysis - S, Chithiraivel; R, Loganayaki; K, Saravanan; R, Sharmila; S, Sivankalai; K, Sivasekaran (International Journal of Membrane Science and Technology, 2023)
The history of exoskeleton-like contraptions traces back to 1890 when Russian inventor Nicholas Yagin created the first passive gadget that required human intervention. Over the years, academic and industrial organizations have shown great interest, resulting in numerous studies, prototypes, and commercialized products. In this publication, we present a scientometrics investigation focusing on exoskeleton research. The analysis encompasses exoskeleton publications published from 1989 to 2022 year. Various scientometrics metrics were employed to explore different aspects of the field, including authors, nations, affiliations, keywords, citations, and collaboration networks. Among the Nation’s leading in this sector, the United States stands at the forefront with an extensive collaboration network involving other countries. Harvard University emerges as a critical contributor to exoskeleton research, leading in the number of publications, total citations per article (Vitiello N), h-index, g-index, and m-index. Over the past years, the Journal of Neuroengineering and Rehabilitation has experienced a significant surge in manuscripts related to exoskeletons, signifying the growing interest in the field since 2006. According to the author’s keyword analysis, most studies focus on exoskeletons and their uses in rehabilitation. This comprehensive report provides an in-depth assessment of the current state of exoskeleton research and collaboration networks. It is a valuable resource for researchers to guide their projects or discover potential collaborators.